A Data Quality aware Enterprise Service Bus for e-Health Integration Platforms - Pidre, Silvana (2017)
The integration of software systems running in different healthcare organizations is increasingly required in order exchange data and carrying out healthcare processes in coordinated ways. This integration is usually supported by integration platforms which are based on advanced middleware technologies, like the Enterprise Service Bus (ESB). In addition, data quality in the healthcare area is critical to take timely and accurate decisions for the health and well-being of patients. This paper proposes a data quality aware ESB (DQ-ESB) for e-Health integration platforms which allows assessing and enforcing data quality within inter-organizational data exchanges. DQ-ESB handles an extensible data quality model which includes quality characteristics identified within the Uruguayan e-Health context. DQ-ESB provides data quality solutions based on native ESB mechanisms (e.g. data transformation) and it was implemented leveraging the Switchyard ESB product.